Analisis Perkembangan Riset Akuntansi Keperilakuan Studi Pada Jurnal Behavioral Research In Accounting (1998-2003) - Tan Ming Kuang; Se Tin (Universitas Kristen Maranatha, 2010)
This research aims to analyze growth direction of research in journal of BRIA period 1998-2003. Growth analysis is done at topic / article content, research method, and research subject used by writer of article of BRIA 1998-2003. Topic /article content is classified using taxonomy of Birnberg and Shield (1989) which have been modified by Meyer and Rigsby (2001). Technics of descriptive analysis were used to analyze data. The results show that the most frequent topics written in BRIA as long as 1998-2003 is Accounting Information Processing, Auditing, and Managerial Control. Most research method used are experiment (29 articles) and survey/questionaire/interview (21 articles). Type of subject most often used is accountant /auditor and student S-1. As a whole, this result not far differ from result of research of Meyer and Rigsby (2001). Thereby, until 14 year publication of BRIA, there are not growth mean in the case of topic, method, and used research subject. This results show that we still have opportunities of doing new research in order to development of behavioral accountancy science. Keywords: growth direction of research, BRIA 1998-2003.